2021
DOI: 10.1371/journal.pone.0259299
|View full text |Cite|
|
Sign up to set email alerts
|

Batch-produced, GIS-informed range maps for birds based on provenanced, crowd-sourced data inform conservation assessments

Abstract: Accurate maps of species ranges are essential to inform conservation, but time-consuming to produce and update. Given the pace of change of knowledge about species distributions and shifts in ranges under climate change and land use, a need exists for timely mapping approaches that enable batch processing employing widely available data. We develop a systematic approach of batch-processing range maps and derived Area of Habitat maps for terrestrial bird species with published ranges below 125,000 km2 in Centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 22 publications
(18 reference statements)
1
46
0
Order By: Relevance
“…through the consideration of elevational ranges or measures of spatial distance (e.g. Huang et al, 2021, Palacio et al, 2021. However, we herein focused on a simple and readily applicable approach to provide a solution most useful for poorly documented species and that avoids circularity with environmental niche models (e.g., SDMs).…”
Section: Ecoregional Range Maps (Ecorms) -Original and Simplifiedmentioning
confidence: 99%
See 2 more Smart Citations
“…through the consideration of elevational ranges or measures of spatial distance (e.g. Huang et al, 2021, Palacio et al, 2021. However, we herein focused on a simple and readily applicable approach to provide a solution most useful for poorly documented species and that avoids circularity with environmental niche models (e.g., SDMs).…”
Section: Ecoregional Range Maps (Ecorms) -Original and Simplifiedmentioning
confidence: 99%
“…However, given the immense workload to produce ExpRMs, the limited number of experts available to inform them, and the sheer number of species on Earth, there is an increasing interest in automating and facilitating their production. Specifically, several recent studies suggested the use of MCVs or similar approaches as surrogates for species' ranges (Dauby et al, 2017;Huang et al, 2021;Palacio et al, 2021). Nevertheless, to our knowledge, their performance has not been evaluated before.…”
Section: Mcvs As Range Surrogatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing current and potential distribution helps conservation action in known localities and directs future searches for sites with a high probability of occurrence. Accurate species distribution models and maps are increasingly proposed to support conservation decision-making (Guisan et al 2013, Huang et al 2021). These also contribute to assessing the species extinction risk by adding important information to this process, such as the size of the population, area of occupancy and occurrence, and locations (IUCN 2022), and contribute to protected area design and establishment.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, GIS datasets that map elevations and the extent of habitats, especially forest cover, have also improved. These advances in species' observations and measurement of habitat now allow us to assess better where species occur, which are at risk, and where conservation priorities lie (Huang et al, 2021).…”
mentioning
confidence: 99%